Peripheral Inflammatory Markers and Suicidal Behavior in Depressive and Anxiety Disorders: A Systematic Review and Meta-Analysis of Neutrophil-to-Lymphocyte, Platelet-to-Lymphocyte, and Monocyte-to-Lymphocyte Ratios - Ni Made Citra Riesti Wulan; Wayan Wiradana (Scientia Psychiatrica, 2025)
Introduction: Suicidal behavior is a major public health crisis, intricately linked with depressive and anxiety disorders. A growing body of evidence implicates systemic inflammation in the pathophysiology of these conditions and suicidality. This systematic review and meta-analysis aims to synthesize the evidence on the association between accessible peripheral inflammatory markers—neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR)—and suicidal behavior in patients with depressive or anxiety disorders. Methods: A systematic literature search was conducted in PubMed, Cochrane, ScienceDirect, Ebsco, and SpringerLink for observational studies up to March 2024. Studies comparing NLR, PLR, or MLR between patients with depressive or anxiety disorders with suicidal behavior and those without were included. Data were pooled using a random-effects model. The primary outcomes were the standardized mean difference (SMD) for NLR and mean difference (MD) for PLR and MLR. Results: Thirteen studies comprising 2,392 patients (1,192 with suicidal behavior, 1,200 controls) were included. The analysis revealed that patients with suicidal behavior had significantly higher NLR (Standardized Mean Difference [SMD] = 0.55; 95% CI: 0.26–0.84; p < 0.001), PLR (Mean Difference [MD] = 11.31; 95% CI: 7.48–15.14; p < 0.00001), and MLR (MD = 0.02; 95% CI: 0.01–0.03; p < 0.00001) compared to non-suicidal patients. Significant heterogeneity was observed in the NLR analysis (I2 = 90%). Conclusion: This meta-analysis establishes a significant association between elevated peripheral inflammatory markers (NLR, PLR, MLR) and suicidal behavior in patients with depressive and anxiety disorders. These findings support the inflammatory hypothesis of suicidality. However, substantial heterogeneity and methodological limitations across studies necessitate cautious interpretation. These markers represent promising areas for future research but are not yet suitable for clinical risk prediction.